2009
DOI: 10.1021/jf902075b
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Stress Response of Macrolepiota procera to Nickel

Abstract: Nickel (Ni) is an essential element for many organisms; however, it is very toxic at high concentrations and also depending on the species. In macrofungi the mechanisms underlying their Ni tolerance are poorly documented. This study examines, for the first time, the participation of the antioxidative system in Macrolepiota procera exposed to different Ni2+ concentrations and their relation with Ni tolerance. The effect of the pH on Ni tolerance was also evaluated. The fungus was cultivated on solid medium with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…For some of the sampled sites, Ag and Hg were highly bioconcentrated by M. procera and their BCF values reached more than 100. Earlier studies reported that M. procera has the ability to efficiently bioconcentrate Hg [54][55][56][57]. This species, apart from being rich in the essential elements (including Cu and Zn), is also rich in Cd, Pb, Hg, and Ag [2,14,26,40,56].…”
Section: Resultsmentioning
confidence: 99%
“…For some of the sampled sites, Ag and Hg were highly bioconcentrated by M. procera and their BCF values reached more than 100. Earlier studies reported that M. procera has the ability to efficiently bioconcentrate Hg [54][55][56][57]. This species, apart from being rich in the essential elements (including Cu and Zn), is also rich in Cd, Pb, Hg, and Ag [2,14,26,40,56].…”
Section: Resultsmentioning
confidence: 99%
“…For the highest doses of fungicides (2RD), copper content in B. bassiana decreased. It is known that fungi are able to accumulate significant amounts of metals (Gadd 1993;Figueiredo et al 2007;Baptista et al 2009), including entomopathogenic fungi (Popowska-Nowak et al 2004;Fomina et al 2005b). Although B. bassiana was able to solubilize copperbased fungicides, and therefore increase copper bioavailability and toxicity, this strain has shown high tolerance to those fungicides, especially to copper hydroxide and copper oxychloride.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of these results, without considering element speciation in fungi, As and Ni values in our samples are within actual background level ranges for mushrooms collected in unpolluted areas. Ni speciation in soils and macrofungi is of actual interest: increasing concentrations of the element induce an oxidative stress response in M. procera mycelium cultivated in Petri dishes, counter-balanced by superoxide dismutase and catalase activities (Baptista et al 2009). …”
Section: As and Nimentioning
confidence: 99%